Hubungan Motivasi Belajar Matematika dan Kemampuan Numerasi Siswa Kelas III SDN Ketawang 2 - Isroviana Ardani Putri; Kartinah Kartinah; Sunan Baedowi (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
Motivation to learn mathematics is closely related to numeracy skills which require mathematical calculations. Students who have high learning motivation will achieve good learning outcomes. The purpose of this study was to determine the motivation to learn mathematics in class III students at SD Negeri Ketawang 2, to determine the numeracy skills and to determine the relationship between motivation to learn mathematics and the numeracy skills of students in class III at SD Negeri Ketawang 2. This type of research is quantitative research with a correlational research design. The data collection technique was carried out by using a questionnaire on mathematics learning motivation and numeracy skills for 25 students as the research sample. The data was then processed and analyzed using the product moment correlation analysis technique with the help of SPSS for windows version 25. The results showed that: (1) students' motivation to learn mathematics was moderate, (2) students' numeracy skills were in a good predicate, (3) there was a significant relationship between mathematics learning motivation and numeracy skills with a correlation coefficient value of 0.837 in the very category strong.